Thermal shock resistance of functionally graded materials with mixed-mode cracks. (1st June 2019) - Zhang, Yanyan; Guo, Licheng; Wang, Xiaoli; Shen, Rilin; Huang, Kai
Abstract: The thermal shock resistance of functionally graded materials (FGMs) is studied in the presence of periodic mixed-mode cracks as characterization of a typical damaging effect of thermal shock loading on FGMs. A methodology of assessing the thermal shock resistance of FGMs is proposed featuring consideration of both strength and fracture theories. The thermal shock resistance is modeled through three distinct failure criteria: (i) the maximum local tensile stress criterion (ii) the maximum thermal stress intensity factor criterion and (iii) the maximum hoop stress criterion. The finite-difference approximation of the transient temperature field is obtained firstly according to Fourier's law of heat conduction. The corresponding thermal stress field is then obtained through the finite element analysis of the mechanical problem involving thermal strain. With such a coupling between the finite element method (FEM) and finite difference method (FDM) resolving the thermomechanical response, the mixed-mode thermal stress intensity factors (TSIFs) are accordingly extracted through the interaction energy integral method (IEIM). Some typical examples of periodic mixed-mode cracks are presented with the influences of crack spacing, crack length and crack angle on the thermal shock resistance of FGMs studied. Furthermore, the distribution patterns of material properties in FGMs are discussed in terms of their effects on the thermal shock resistance. The results indicate that the proposed methodology provides an effective pathway to assessment of thermal shock resistance of FGMs showing great significance in design and fracture evaluation of such materials.